Exergy transfer in a porous rectangular channel - Kurtbas, Irfan; Celik, Nevin; Dincer, Ibrahim (Pergamon-Elsevier Science Ltd, 2010)
Present paper is performed to investigate the heat and exergy transfer characteristics of forced convection flow through a horizontal rectangular channel where open-cell metal foams of different pore densities such as 10, 20 and 30 PPI (per pore inches) were situated. All of the bounding walls of the channel are subjected to various uniform heat fluxes. The pressure drop and heat transfer characteristics are presented by two important parametric values, Nusselt number (Nu(H)) and friction factor (f), as functions of Reynolds number (Re-H) and the wall heat flux (q). The Reynolds number (Re-H) based on the channel height of the rectangular channel is varied from 600 to 33 000, while the Grashof number (Gr(Dh)) ranged from approximately 10(5)-10(7) depending on q. Based on the experimental data, new empirical correlations are constructed to link the Nu(H). The results of all cases are compared to that of the empty channel and the literature. It is found that the results are in good agreement with those cited in the references. The mean exergy transfer Nusselt number (Nu(e)) based on the Re-H, Nu(H), Pr and q for a rectangular channel with constant heat flux is presented and discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aluminum foams; Porous medium; Exergy; Rectangular channel flow